2022
DOI: 10.1155/2022/2863815
|View full text |Cite|
|
Sign up to set email alerts
|

Growth Differentiation Factor-15 Based ABC (Age, Biomarkers, Clinical History)-AF (Atrial Fibrillation)-Bleeding Risk Score for Elderly Patients with Nonvalvular Atrial Fibrillation

Abstract: Background. Growth differentiation factor-15 (GDF-15) is a strong predictor of bleeding in atrial fibrillation (AF) patients. The novel ABC (age, biomarkers, and clinical history), AF, and bleeding risk score outperforms HAS-BLED bleeding risk score for major bleeding (MB) in patients with AF receiving oral anti-coagulation in the clinical trial cohort. However, it has not been entirely externally validated. We aimed to refine and understand the application of the ABC-AF bleeding risk score in elderly (aged ≥6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%